ON REPRODUCTIVE BIOLOGY OF DISTANT HYBRIDS IN THE GROSSULARIACEAE FAMILY - O. A. Gavrilova; O. A. Tikhonova (Труды по прикладной ботанике, генетике и селекции)
Pollen morphology and pollen quality in distant hybrids of the genus Ribes L. were studied in the Russian North-West. A rather high fertility level was found in the studied hybrids, except for the triploid ‘Dlinnokistnaya CGL’. A connection between anomalous morphological features of the pollen wall structure and the pollen fertility level has been found in the studied samples.